Endogenous Tongue Thrust – Myth?. (2nd January 2021) - Lam, Yung; Shelton, Andrew; Sandler, Jonathan
Abstract : Anterior open bite cases are very challenging to manage due to the high relapse potential associated with this feature of malocclusion. It is helpful if the aetiology is established before embarking on treatment to ensure that the appropriate treatment modalities are carried out. Determining whether the aetiology of an anterior open bite is caused by an 'endogenous tongue thrust' is extremely difficult. In particular, differentiating between an adaptive and endogenous tongue thrust can be extremely challenging. The case study presented explores the clinical considerations when diagnosing and treating anterior open bites. CPD/Clinical Relevance: This report raises the question: is it possible to diagnose an endogenous tongue thrust?